BRAND AMBASSADOR DAN BRAND IMAGE PADA MINAT BELI KONSUMEN (STUDI KASUS PENGGUNA SMARTPHONE SAMSUNG DI KOTA PADANG) - Sarah Lazuar Dini; Willy Nofranita; Lola Fitria Sari (Ensiklopedia of Journal, 2023)
This study aims to determine the effect of brand ambassadors and brand image on consumer buying interest, a case study on Samsung smartphone users in Padang City. This research is descriptive research with a quantitative approach. The population and sample in this study were Samsung smartphone users in Padang City, and the number of respondents in the sample in this study was 140 respondents. The data source in this study is the primary data source, and data collection techniques using a questionnaire. The analysis technique uses the Structural Equation Modeling (SEM) method, which is processed using the STATA 17 program. Brand ambassadors and brand image, which are exogenous variables in this study, have an impact on consumer buying interest. This is evidenced by the results obtained in this study showing the probability value brand ambassador is 0.008, and the probability value of brand image is 0.000. This figure shows that brand ambassadors have a significant positive effect on purchase intention, brand ambassadors have a significant positive effect on brand image and brand image has a significant positive effect on purchase intention.Keywords: Brand Ambassador, Brand Image, Purchase Intention